Grammatical Gender and Mutabaqah in Arabic Language Learning: A Conceptual Analysis of Muzakkar and Muannats - Joko Andi Koiruman; Hapizil Umam; Arianto (CV. Jalan Cendikia, 2026)
This article aims to analyze the conceptual problems of muzakkar and muannats in Arabic language learning for non-native speakers. This study employs a library research method using a narrative literature review and conceptual analysis of Arabic grammar, second language acquisition, grammatical gender, and grammar teaching strategies. The findings show that the main problem in learning muzakkar and muannats does not merely lie in the complexity of grammatical rules, but in learners’ tendency to understand gender mechanically as a formal marker or biological category. The major misconceptions include reducing muannats to ta’ marbuthah, equating grammatical gender with biological sex, weak application of mutabaqah, and difficulty identifying gender forms that are not morphologically transparent. These problems are caused by the transfer of Indonesian as a gender-neutral first language, the cognitive load of beginner learners, non-hierarchical teaching materials, and the dominance of memorization-based grammar instruction. This article proposes a conceptual-contextual learning model through contrastive explanation, lexical mapping, gradual mutabaqah practice, meaningful production, and error reflection. The study emphasizes that muzakkar and muannats should be positioned as a fundamental basis for mastering Arabic grammatical structures in an applicable and meaningful way.